The perception of elite athletes' guided self-reflection and performance in archery. Issue 2 (3rd March 2016) - Tan, Si Lie; Koh, Koon Teck; Kokkonen, Marja
Abstract: Self-reflection has been shown to enhance professional development in clinical, counselling and educational settings. Recent research found that self-reflection can enhance performance in elite sports. The purpose of this intervention study was two-fold: Firstly, to examine whether a guided reflective diary was effective in enhancing accuracy in elite archery, and secondly, to identify factors facilitating and hindering the usage of the guided reflective diary. Eight Singaporean elite archers (four females, four males), aged 20–24 years, reflected on their training using the diary for a period of five weeks. Their pre- and post-intervention performance scores were collected and qualitative interviews were conducted. Quantitative data revealed that only two archers improved their performance after the intervention, whereas six performed poorer than before. Qualitative data were content analysed using the thematic method. This revealed three facilitating factors for the guided reflective diary usage: (1) serves as a reminder, (2) description of shooting feeling, and (3) enhances motivation. In contrast, (1) time-consumption, (2) high number of questions, and (3) the repetitive nature of the reflection questions were reported as the three most common hindering factors for the effective usage of the reflective diary. The results are discussed using the sport and coaching science literature. Practical implications are proposed to optimise athletes' use of reflection as a learning tool for personal improvement and performance enhancement.